On the breeding cases of the Levant Sparrowhawk and Shikra on the Mangistau Peninsula, Kazakhstan - Kanatbek Kenzhegulov (Пернатые хищники и их охрана, 2025)
The short report provides information on breeding cases of Shikra (Accipiter badius) and Levant Sparrowhawk (Accipiter brevipes) on the Mangistau (Mangyshlk) Peninsula. Since 2019, the Shikra has been observed breeding in the Aktau Botanical Garden every year. In 2024, the first reliable case of breeding the Levant Sparrowhawk there was recorded.